The Effectiveness of STAD Method Towards Students’ Understanding of Simple Present Tense - Hurairo, Eti Widiya; Iman, Jaya Nur; Angraini, Nike Angraini (Universitas Nurul Jadid, 2023)
Understanding grammar is essential for students learning English as a foreign language. Grammar rules provide order and clarity to the language so that students could understand how words, phrases and sentences are combined. According to Ameilani (2019),